KAJIAN KESESUAIAN POLA RUANG VEGETASI PESISIR TERHADAP MITIGASI BENCANA TSUNAMI DI KECAMATAN MEURAXA KOTA BANDA ACEH - Sabaruddin .; Mirza .; Izziah . (Jurnal Ilmu Kebencanaan : Program Pascasarjana Unsyiah, 2016)
Coastal region which little vegetation, tsunami waves can reach dozen kilometers to mainland, while region having good vegetation coverage, the extent  damage is lighter. Research objectives are (1) to see rendering vegetation coastal with concept disaster mitigation with the Spatial Plan Area (RTRW) 2009-2029 in district Meuraxa. (2) The development coastal vegetation composition for tsunami disaster mitigation in district Meuraxa. This research uses descriptive qualitative. In district Meuraxa, there are several types plants include Mangrove (Rhizopora), Api-api (Avicevia germinans), Sea Pine (Casuarina equisetifolia L), Ketapang (Terminalia catappa L) which have  important role in addressing the wide range threats, among other disasters such  the tsunami, coastal abrasion, anchoring waves, windbreaks. Preparation pattern space RTRW 2009-2029 in district Meuraxa consists  8 (eight) parameter dominated by water space 172.596 Ha (41.35%), residential area  60.963 Ha (14.61%), the open green space area  8.475 Ha (2.03%), mangrove forest  90.595 Ha (21.71%) from total area. The existing  space consists 9 (nine) parameter dominated by water space 172.596 Ha (41.35%), residential area 83.173 Ha (19.93%), open green space area 39.822 Ha (9.54%), mangrove forest  78.652 Ha (18.85%) from the total areas space there is the addition  pond area 5.521 Ha (1.32%).